2011
DOI: 10.1002/prot.23135
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of function in strictosidine synthase‐like proteins

Abstract: The exponential growth of sequence data provides abundant information for the discovery of new enzyme reactions. Correctly annotating the functions of highly diverse proteins can be difficult, however, hindering use of this information. Global analysis of large superfamilies of related proteins is a powerful strategy for understanding the evolution of reactions by identifying catalytic commonalities and differences in reaction and substrate specificity, even when only a few members have been biochemically or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 69 publications
0
32
0
2
Order By: Relevance
“…Even a reasonable fallback position requires the development of new strategies for identifying the few experiments that could be most useful for validation of large-scale computational predictions. As illustrated here and elsewhere (44,45), protein similarity networks represent one way to generate the context needed for choosing those experiments and interpreting the results.…”
Section: Challenges For Computational Prediction Of Functional Propermentioning
confidence: 99%
“…Even a reasonable fallback position requires the development of new strategies for identifying the few experiments that could be most useful for validation of large-scale computational predictions. As illustrated here and elsewhere (44,45), protein similarity networks represent one way to generate the context needed for choosing those experiments and interpreting the results.…”
Section: Challenges For Computational Prediction Of Functional Propermentioning
confidence: 99%
“…They presented protein similarity networks (PSNs) to fulfill this need [22]. PSNs have contributed to our understanding of a number of large groups of proteins including the enolase superfamily [23], the ePK-like superfamily [24], glutathione transferases [25], [26], strictosidine synthase-like proteins [27], cysteine peptidases [28], and proteins used in algal metal transport [29]. These studies have yielded meaningful insights, validated PSN methodology, and provided an understanding of the caveats and limitations of PSNs.…”
Section: Introductionmentioning
confidence: 99%
“…First, although MEC-6 did not affect MEC-4 abundance in Xenopus oocytes, loss of mec-6 in vivo led to a drastic reduction in MEC-4::YFP expression in the TRNs (8). Second, studies in Drosophila melanogaster found that, although DEG/ENaC proteins needed for mechanosensation were present (14-18), obvious MEC-6-like proteins were not (19). Third, we wondered about the importance of the puncta and the apparent colocalization of the proteins in them, because in vivo electrophysiological studies of the TRNs (5) showed that the estimated number of active channels equaled the number of puncta, but single channels were unlikely to be visible by fluorescence microscopy.…”
mentioning
confidence: 99%